2003
DOI: 10.1159/000073203
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Scan for Loci Affecting Normal Adult Height in the Framingham Heart Study

Abstract: Objective: To map loci influencing normal adult height in 335 families from the Framingham Heart Study. Methods: We analyzed data consisting of 1,702 genotyped individuals who have been followed over time. The first height measurement for individuals between the ages 20–55 years was analyzed in a genome-wide scan using variance component linkage analysis. Sex, age, and cohort effects were removed before analysis. Results: Two regions (18pter-p11, 22q11.2) with multipoint LOD scores >1.0 (–log p values >2.0) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
(41 reference statements)
4
15
3
Order By: Relevance
“…We have identified major loci for height on chromosomes 15, 8 and 3, and a locus for BMI on chromosome 4. We did not detect a significant linear correlation between height and age, although other studies have shown an inverse relationship with age (Mukhopadhyay et al 2003). Since we used self-reported height, participants in our study may be reporting a height measurement recalled from an age period different to their current height.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…We have identified major loci for height on chromosomes 15, 8 and 3, and a locus for BMI on chromosome 4. We did not detect a significant linear correlation between height and age, although other studies have shown an inverse relationship with age (Mukhopadhyay et al 2003). Since we used self-reported height, participants in our study may be reporting a height measurement recalled from an age period different to their current height.…”
Section: Discussioncontrasting
confidence: 65%
“…Previous studies have frequently reported heritability estimates in excess of 0.6 for height (e.g., Hirschhorn et al 2001;Perola et al 2001;Deng et al 2002;Wiltshire et al 2002;Xu et al 2002;Mukhopadhyay et al 2003;Wu et al 2003). In African Americans, heritability estimates have been reported to be as high as 0.87 (Luke et al 2001), and the multi-ethnic range of heritability reported by Wu et al (2003) of 0.75-0.98 included an African American sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the list of genes and allelic variants involved in the determination of BS and BG variation is far from being complete. Several genome-wide scans have been conducted to identify susceptibility loci for bone size (e.g., Koller et al 2001;Deng et al 2003b) and adult height variation (e.g., Mukhopadhyay et al 2003;Willemsen et al 2004). With a few exceptions the results of the linkage analyses are so far largely inconsistent.…”
Section: Introductionmentioning
confidence: 99%